Strategi Manajemen Kurikulum dalam Pengendalian Mutu Lulusan di Madrasah Muallimin Muallimat Bahrul Ulum Tambakberas Jombang - Wafa, M Aliyul; Iffah, Bidayatul Hubbil (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
Quality is the main indicator for schools to be able to achieve goals and public trust. Achieving the quality of educational institutions cannot be separated from the curriculum management strategy, where the curriculum management strategy also functions to maintain the existence of educational quality by quality control. This research aims to determine curriculum management strategies in controlling the quality of graduates at Madrasah Muallimin Muallimat Pondok Pesantren Bahrul Ulum Tambakberas Jombang. The method used by researchers in this research is a descriptive qualitative method with primary and secondary data sources. The data collection procedures used in this research include observation, interviews and documentation with data collection, reduction, display and verification analysis techniques. The results of this research show that: (1) The management strategy implemented by Madrasah Muallimin Muallimat in controlling the quality of graduates , is by implementing a 5 year strategic plan. organizing, implementing and controlling which involves all elements of the madrasah starting from the madrasah head to the students. (2) In carrying out graduate quality control, Madrasah Muallimin Muallimat also carries out quality planning, quality control and quality improvement which is realized in the form of curriculum programs. Based on the research findings. It can be concluded that the curriculum management strategy in quality control is an effort made by educational institutions to maintain the existence of the educational quality that has been achieved.